Effect of Ni on growth kinetics, microstructural evolution and crystal structure in the Cu(Ni)–Sn system. Issue 21 (23rd July 2017) - Baheti, Varun A.; Kashyap, Sanjay; Kumar, Praveen; Chattopadhyay, Kamanio; Paul, Aloke
Abstract: The role of Ni addition in Cu on the growth of intermetallic compounds in the Cu–Sn system is studied based on microstructure, crystal structure and quantitative diffusion analysis. The diffraction pattern analysis of intermetallic compounds indicates that the presence of Ni does not change their crystal structure. However, it strongly affects the microstructural evolution and diffusion rates of components. The growth rate of (Cu, Ni)3 Sn decreases without changing the diffusion coefficient because of the increase in growth rate of (Cu, Ni)6 Sn5 . For 3 at.% or higher Ni addition in Cu, only the (Cu, Ni)6 Sn5 phase grows in the interdiffusion zone. The elongated grains of (Cu, Ni)6 Sn5 are found when it is grown from (Cu, Ni)3 Sn. This indicates that the newly formed intermetallic compound joins with the existing grains of the phase. On the other hand, smaller grains are found when this phase grows directly from Cu in the absence of (Cu, Ni)3 Sn indicating the ease of repeated nucleation. Grain size of (Cu, Ni)6 Sn5 decreases with further increase in Ni content, which indicates a further reduction of activation barrier for nucleation. The relations for the estimation of relevant diffusion parameters are established considering the diffusion mechanism in the Cu(Ni)–Sn system, which is otherwise impossible in the phases with narrow homogeneity range in a ternary system. The flux of Sn increases, whereas the flux of Cu decreases drastically with the addition of very small amount of Ni, such as 0.5 at.% Ni, in Cu. Analysis of the atomic mechanism of diffusion indicates the contribution from both lattice and grain boundary for the growth of (Cu, Ni)6 Sn5 phase.